Microsystems dynamics - Ostasevicius, Vytautas; Dauksevicius, Rolanas; SpringerLink (Online service). (New York Springer, 2011)
In recent years microelectromechanical systems (MEMS) have emerged as a new technology with enormous application potential. MEMS manufacturing techniques are essentially the same as those used in the semiconductor industry, therefore they can be produced in large quantities at low cost. The added benefits of lightweight, miniature size and low energy consumption make MEMS commercialization very attractive. Modeling and simulation is an indispensable tool in the process of studying these new dynamic phenomena, development of new microdevices and improvement of the existing designs. MEMS technology is inherently multidisciplinary since operation of microdevices involves interaction of several energy domains of different physical nature, for example, mechanical, fluidic and electric forces. Dynamic behavior of contact-type electrostatic microactuators, such as a microswitches, is determined by nonlinear fluidic-structural, electrostatic-structural and vibro-impact interactions. The latter is particularly important: Therefore it is crucial to develop accurate computational models for numerical analysis of the aforementioned interactions in order to better understand coupled-field effects, study important system dynamic characteristics and thereby formulate guidelines for the development of more reliable microdevices with enhanced performance, reliability and functionality.
Foreword -- Preface -- Introduction to Microsystems -- Fabrication Technologies of Microsystems -- Overview -- Nickel Surface Micromachining Technology for Fabrication of Microswitches -- UV Lithography for Fabrication of Micromotors -- Common MEMS Actuators -- Parallel Plate Capacitors -- Comb Drives -- Electrostatic Micromotors -- Electrostatic Microswitches -- Theoretical Background of Multiphysical Interactions Common in Microsystems -- Introduction to Coupled-Field Modeling -- Electrostatic Actuation and Pull-in Instability -- Viscous Air Damping -- Vibro-Impact Interactions -- Experimental Testing of Microsystem Dynamics -- Vibration Excitation Methods -- Optical Techniques for Measurement of Vibrations of Microstructures -- Study of Elastic Vibro-Impact Macrosystems and Microsystems -- Overview of Important New Effects of Nonlinear Dynamics in Vibro-Impact -- Macrosystems -- -- Analysis of Coupled-Field Dynamics in Contact-Type Electrostatic Microactuator -- Numerical Modeling and Analysis of Fluidic-Structural Interaction -- Numerical Modeling and Analysis of Electrostatic-Structural Interaction -- Numerical Modeling and Analysis of Vibro-Impact Interaction -- Numerical Analysis of the Micromotor -- Finite Element Modeling of Micromotor -- Modal Analysis -- Micromotor Control -- Analytical Model of a Micromotor -- Basics of Micromotor Geometry -- Torque Analysis -- Micromotor Design Guidelines -- References.
Electronic reproduction.
Keywords: Nanotechnology; Microelectromechanical systems; Industrial design; Electronic books